2018
DOI: 10.1111/ocr.12254
|View full text |Cite
|
Sign up to set email alerts
|

Is Short Root Anomaly (SRA) a risk factor for increased external apical root resorption in orthodontic patients? A retrospective case control study using cone beam computerized tomography

Abstract: Structured AbstractObjectives: To evaluate the amount of external apical root resorption (EARR) secondary to orthodontic treatment in patients with Short Root Anomaly (SRA) compared to patients with average root lengths using Cone Beam Computed Tomography (CBCT). Settings and Sample Population:Cone beam computed tomography scans of 23 SRA and 26 control patients were selected from 232 pretreatment scans from a single private practice. Materials and Methods:Cone beam computed tomography scans before (T1) and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Orthodontic treatment was satisfactorily completed with sufficient overjet, overbite, incisor angulation and stable posterior occlusion. The posttreatment IOPA and panoramic radiograph revealed unaltered root morphology with adequate bone support, implying that orthodontic treatment is not an absolute contraindication in asymptomatic SRA5 15 21–23 (figure 2). The patient will be followed up over the next 5 years on a 6-month interval to monitor the prognosis of the tooth.…”
Section: Descriptionmentioning
confidence: 99%
“…Orthodontic treatment was satisfactorily completed with sufficient overjet, overbite, incisor angulation and stable posterior occlusion. The posttreatment IOPA and panoramic radiograph revealed unaltered root morphology with adequate bone support, implying that orthodontic treatment is not an absolute contraindication in asymptomatic SRA5 15 21–23 (figure 2). The patient will be followed up over the next 5 years on a 6-month interval to monitor the prognosis of the tooth.…”
Section: Descriptionmentioning
confidence: 99%
“…A study on healthy Finnish young adults found a prevalence of SRA of 1.3% [ 3 ]. Cutrera et al [ 7 ] reported a prevalence of almost 10% in a sample of 232 patients evaluated for orthodontic treatment; however, the majority of these patients were of Hispanic origin. Moreover, several studies agree that SRA is almost three times more common in females (1 : 2.5–1 : 3.6) [ 1 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%